Transport infrastructure environmental performance: the role of stakeholders, technological integration, government policies and lean supply chain management - Fan, Jianqiang; Mehmood, Saqib; Hussain, Iftikhar; Nazir, Samera; Basit, Abdul (Frontiers in Environmental Science, 2023)
The recent past is characterized by heightened environmental awareness, enhancing the environmental performance of transportation infrastructure was of utmost importance. The central purpose of this study was to delve into and comprehend methods for improving the environmental performance of transportation infrastructure. It aimed to investigate three pivotal factors: engagement of stakeholders, integration of technology and formulation of government policies. Furthermore, the study emphasized exploring how Lean Supply Chain Management could act as a facilitator in accomplishing these enhancements. The study's approach involved a mediation analysis, utilizing quantitative methods to collect data from 89 construction firms operating in Pakistan. The customized questionnaire was employed to gather the necessary data, and employed random sampling techniques to select participants. The hypotheses were tested through partial least squares (PLS 4) analysis. The findings of this study highlighted that stakeholder, including government entities, private enterprises, and local communities, significantly shape the environmental outcomes of transport projects. It explored how technological integration influences environmental performance and assesses the effectiveness of current government policies in promoting sustainability. The study also examined the role of lean supply chain management practices. Implications stressed the importance of stakeholder collaboration, 2 This is a provisional file, not the final typeset article the integration of innovative technologies and policies, refining regulations for sustainability goals and adopting a holistic approach for enhancing overall environmental performance in the transport sector.